2022
DOI: 10.3389/fsurg.2022.963399
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Diffuse idiopathic skeletal hyperostosis with ossification of the posterior longitudinal ligament in the cervical spine: A rare case with dysphagia and neurological deficit and literature review

Abstract: Diffuse idiopathic skeletal hyperostosis (DISH) is characterized by the calcification and ossification of ligaments and tendons. Progressive dysphagia caused by DISH-related anterior cervical osteophytes and deteriorating dysphagia caused by DISH combined with neurological dysfunction resulting from the posterior longitudinal ligament is rare. The initial diagnosis is misleading and patients often consult several specialists before spine surgeons. This study aims to provide a comprehensive review of the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The treatment plans made by inexperienced clinicians may fail to provide interventions in time and result in unexpected pain. Studies reported that progressive symptoms caused by anterior osteophytes are easily missed during the early evaluation 25 . When severe and unexpected pain develops due to untimely treatment, surgery is required to remove the osteophyte 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The treatment plans made by inexperienced clinicians may fail to provide interventions in time and result in unexpected pain. Studies reported that progressive symptoms caused by anterior osteophytes are easily missed during the early evaluation 25 . When severe and unexpected pain develops due to untimely treatment, surgery is required to remove the osteophyte 26 .…”
Section: Discussionmentioning
confidence: 99%